Hormonal responses to training and its tapering off in competitive swimmers: relationships with performance - Mujika, I.; Chatard, J. C.; Padilla, S.; Guezennec, C. Y.; Geyssant, A. (European Journal of Applied Physiology, 1996)
The results showed that the monitored plasma hormones and metabolic indices were unaltered by 12 weeks of intense training and 4 weeks of taper. The T (total testosterone) : C (cortisol) and NSBT (non-sex hormone binding globulin-bound-testosterone) : C ratios, however, appeared to be effective markers of the swimmers' performance capacities throughout the training season.